PROTOTYPING OF BUKHARA CULINARY APPLICATION - Tukhtayev, Umidjon; Hanum, Yuhilza (Universitas Gunadarma, 2021)
The purpose of this research is to build a prototype of Bukhara Culinary Application using informal prototyping method. The difference between this application and the existing ones is the availability of ingredients and history information. This application will also provide delivery service to the customers. Customers and drivers register to this application, so that their details will be recorded. This might not seem much different from the available applications, but this research is also conducted to portray the use of informal prototyping. It is used for the ease in accommodating changes and continuing to the next step of software development by using commonly used software such as Adobe Photoshop. This research resulted in a prototype that provide the described information for 17 dishes from 5 restaurants in Bukhara.